Development of Intermediate Media for Snakes and Ladders Multiplication and Division for Understanding Mathematics Class III State Primary School 1 Banjar Tengah - Astika Dewi, Made Sri; Nurgiansah, T Heru (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The facilities formulated regarding this analysis contain visual learning intermediaries which include game boards, question cards related to multiplication and division, material cards, dice, and pawns (students). This research aims to develop learning media and determine the feasibility, practicality and effectiveness of this method. The development method used in this research is the development model A D D I E, "Analysis, design, development, Implementation, and Evaluation". In this case, the data collection pattern of questionnaires and tests is used. There are two data analysis techniques in this research, namely quantitative analysis and qualitative descriptive. Intermediary media for multiplication and division should be used, this is explained because it has been proven by the validator. The agent of multiplication and division snakes and ladders explains that it is very efficient based on the results questionnaire student and teacher responses. The snakes and ladders medium of multiplication and division was also stated to be effective in students' understanding of mathematical concepts. This is proven by the average value of the pretest and posttest. So the results obtained were that the development of snake and ladder intermediate learning media for multiplication and division was declared feasible, practical and effective in supporting the understanding of mathematical concepts for class III students at SD Negeri 1 Banjar Tengah.